The vinculin-DeltaIn20/21 mouse: characteristics of a constitutive, actin-binding deficient splice variant of vinculin. - Susanna Marg; Ulrike Winkler; Marcello Sestu; Mirko Himmel; Madeleine Schönherr; Janina Bär; Amrit Mann; Markus Moser; Claudia T Mierke; Klemens Rottner; Manfred Blessing; Johannes Hirrlinger; et al. (PLoS ONE, 2010)
Background The cytoskeletal adaptor protein vinculin plays a fundamental role in cell contact regulation and affects central aspects of cell motility, which are essential to both embryonal development and tissue homeostasis. Functional regulation of this evolutionarily conserved and ubiquitously expressed protein is dominated by a high-affinity, autoinhibitory head-to-tail interaction that spatially restricts ligand interactions to cell adhesion sites and, furthermore, limits the residency time of vinculin at these sites. To date, no mutants of the vinculin protein have been characterized in animal models. Methodology/principal findings Here, we investigate vinculin-DeltaEx20, a splice variant of the protein lacking the 68 amino acids encoded by exon 20 of the vinculin gene VCL. Vinculin-DeltaEx20 was found to be expressed alongside with wild type protein in a knock-in mouse model with a deletion of introns 20 and 21 (VCL-DeltaIn20/21 allele) and shows defective head-to-tail interaction. Homozygous VCL-DeltaIn20/21 embryos die around embryonal day E12.5 showing cranial neural tube defects and exencephaly. In mouse embryonic fibroblasts and upon ectopic expression, vinculin-DeltaEx20 reveals characteristics of constitutive head binding activity. Interestingly, the impact of vinculin-DeltaEx20 on cell contact induction and stabilization, a hallmark of the vinculin head domain, is only moderate, thus allowing invasion and motility of cells in three-dimensional collagen matrices. Lacking both F-actin interaction sites of the tail, the vinculin-DeltaEx20 variant unveils vinculin's dynamic binding to cell adhesions independent of a cytoskeletal association, and thus differs from head-to-tail binding deficient mutants such as vinculin-T12, in which activated F-actin binding locks the protein variant to cell contact sites. Conclusions/significance Vinculin-DeltaEx20 is an active variant supporting adhesion site stabilization without an enhanced mechanical coupling. Its presence in a transgenic animal reveals the potential of splice variants in the vinculin gene to alter vinculin function in vivo. Correct control of vinculin is necessary for embryonic development.